C‐Abl‐induced Olig2 phosphorylation regulates the proliferation of oligodendrocyte precursor cells. Issue 6 (13th February 2022) - Zhang, Jun; Sun, Jian‐guang; Xing, Xiaowen; Wu, Rong; Zhou, Lujun; Zhang, Ying; Yuan, Fang; Wang, Shukun; Yuan, Zengqiang
Abstract: Oligodendrocytes (OLs), the myelinating cells in the central nervous system (CNS), are differentiated from OL progenitor cells (OPCs). The proliferation of existing OPCs is indispensable for myelination during CNS development and remyelination in response to demyelination stimulation. The transcription factor Olig2 is required for the specification of OLs and is expressed in the OL lineage. However, the post‐translational modification of Olig2 in the proliferation of OPCs is poorly understood. Herein, we identified that c‐Abl directly phosphorylates Olig2 mainly at the Tyr137 site, and that Olig2 phosphorylation is essential for OPC proliferation. The expression levels of c‐Abl gradually decreased with brain development; moreover, c‐Abl was highly expressed in OPCs. OL‐specific c‐Abl knockout at the developmental stage led to an insufficient proliferation of OPCs, a decreased expression of myelin‐related genes, and myelination retardation. Accordingly, a c‐Abl‐specific kinase inhibitor suppressed OPC proliferation in vitro. Furthermore, we observed that OL‐specific c‐Abl knockout reduced OPC proliferation and remyelination in a cuprizone model of demyelination. In addition, we found that nilotinib, a clinically used c‐Abl inhibitor, decreased the expression of myelin basic protein (Mbp) and motor coordination in mice, indicating a neurological side effect of a long‐term administration of the c‐Abl inhibitor. Thus, we identified the important role of c‐Abl in OLs during developmental myelination and remyelination in a disease model. Main Points: c‐Abl deficiency leads to developmental hypomyelination and delayed remyelination after injury. c‐Abl promotes Olig2 homodimerization via phosphorylation of Olig2 at the Y137 site, which promotes oligodendrocyte precursor cell proliferation.